Contact mechanics of the human finger pad under compressive loads - Dzidek, Brygida M; Adams, Michael J; Andrews, James W; Zhang, Zhibing; Johnson, Simon A (Journal of the Royal Society interface, 2017)
The coefficient of friction of most solid objects is independent of the applied normal force because of surface roughness. This behaviour is observed for a finger pad except at long contact times (greater than 10 s) against smooth impermeable surfaces such as glass when the coefficient increases with decreasing normal force by about a factor of five for the load range investigated here. This is clearly an advantage for some precision manipulation and grip tasks. Such normal force dependence is characteristic of smooth curved elastic bodies. It has been argued that the occlusion of moisture in the form of sweat plasticises the surface topographical features and their increased compliance allows flattening under an applied normal force, so that the surfaces of the fingerprint ridges are effectively smooth. While the normal force dependence of the friction is consistent with the theory of elastic frictional contacts, the gross deformation behaviour is not and, for commonly reported values of the Young's modulus of , the deformation of the ridges should be negligible compared with the gross deformation of the finger pad even when fully occluded. This paper describes the development of a contact mechanics model that resolves these inconsistencies and is validated against experimental data.